Outdoor Activity: Benefits and Risks to Recreational Runners during the COVID-19 Pandemic - Makruf, Aswar; Ramdhan, Doni Hikmat (Kesmas, 2021)
Running has become one of the most popular recreational sports worldwide. It is an easily accessible form of exercise as there are minimal equipment andsport structure requirements. Aerodynamic simulation experiments showed a risk of droplet exposure between runners when two people run in a straight lineat a close distance (slipstream). Thus, running activities require a safe physical distance of 10 meters to avoid droplet exposure, which can be a source oftransmission of COVID-19 infection. However, running outdoors during the COVID-19 pandemic is still often done in pairs and even in groups without wearinga mask. Open window theory stated that changes in the immune system occur immediately after strenuous physical activity. Many immune system componentsshowed adverse changes after prolonged strenuous activity lasting more than 90 minutes. These changes occurred in several parts of the body, such as theskin, upper respiratory tract, lungs, blood, and muscles. Most of these changes reflected physiological stress and immunosuppression. It is thought that an“open window” of the compromised immune system occurs in the 3–72-hour period after vigorous physical exercise, where viruses and bacteria can gain afoothold, increasing the risk of infection, particularly in the upper respiratory tract. Outdoor physical activity positively affects psychological, physiological, biochemical health parameters, and social relationships. However, this activity requires clear rules so that the obtained benefits can be more significant while simultaneously minimizing the risk of transmission of COVID-19 infection.